2023
DOI: 10.1016/j.jht.2021.07.001
|View full text |Cite
|
Sign up to set email alerts
|

A follow up survey on the impact of COVID-19 on hand therapy practice

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Telehealth was more likely to be utilized in urban settings compared to suburban or rural settings. 38 This reinforces the importance of exploring patient satisfaction with this service delivery method, especially as hand therapists generally employ therapeutic touch in a typical therapy session and feel that it is an important factor in patients achieving successful outcomes. 2 High patient satisfaction scores demonstrate that telehealth in an outpatient hand therapy setting is a reasonable method of delivery of care.…”
Section: Discussionmentioning
confidence: 79%
“…Telehealth was more likely to be utilized in urban settings compared to suburban or rural settings. 38 This reinforces the importance of exploring patient satisfaction with this service delivery method, especially as hand therapists generally employ therapeutic touch in a typical therapy session and feel that it is an important factor in patients achieving successful outcomes. 2 High patient satisfaction scores demonstrate that telehealth in an outpatient hand therapy setting is a reasonable method of delivery of care.…”
Section: Discussionmentioning
confidence: 79%
“…Six studies were performed in the United States of America. [21][22][23][24][25][26] Four studies were performed in Australia [27][28][29][30] and three in the United Kingdom. [31][32][33] Two studies each were performed in Sweden, 34,35 Spain 36,37 and Canada.…”
Section: Countries Where Studies Were Performedmentioning
confidence: 99%
“…One study noted the use of various platforms 38 and four studies did not state which software was used. 24,[33][34][35] Bespoke programmes were used because they incorporated specialised software 23,27,29 or because they had increased security. 25,30,39 While well-known programmes are easy to use and familiar to patients, there are concerns about their usability in telehealth provision as they may not meet national privacy and security standards, such as the EU's General Data Protection Regulation.…”
Section: Delivery and Structure Of Virtual Consultationsmentioning
confidence: 99%
“…Literature published since the start of the pandemic, specific to hand therapy telehealth services, has primarily focused on the therapist experience of providing telehealth. 4 , 5 , 6 , 7 Szekeres and Valdes’ 7 survey of 819 therapists early in the COVID-19 pandemic (May 2020), that recruited from hand therapy associations in the United States, Canada, Australia and Europe, showed that very few therapists (n=38, 5%) had telehealth experience prior to the pandemic. The majority of therapists (n=557, 68%) reported they would be extremely or somewhat likely to continue with telehealth sessions once the pandemic settles.…”
Section: Introductionmentioning
confidence: 99%
“… 4 The authors conducted a follow up survey between December 2020 and January 2021. 6 Despite telehealth usage rates increasing to 46% during the first survey period, they had reduced to 29% at this second timepoint, with respondents questioning the “efficiency, effectiveness and reimbursement” (p.8) of telehealth services. 6 These authors discussed that the success of telehealth relies on the availability of infrastructure, including technology, funding and training, as well as clear guidelines for determining when telehealth should be used, based on patient characteristics and diagnoses.…”
Section: Introductionmentioning
confidence: 99%